Escalation in the war in Ukraine lessons learned and risks for the future - Frederick, Bryan; Cozad, Mark R.; Stark, Alexandra (RAND Corporation, 2023)
Despite the devastating losses experienced by the Russian military and both the Ukrainian military and civilian population following Russia's February 2022 invasion of Ukraine, both sides have refrained from pursuing several escalatory options to date. Although Russia has escalated its attacks on Ukraine in several ways, including strikes against critical infrastructure and the civilian population, it has refrained from other options--notable given the high stakes for the Kremlin and the potential capabilities Russia could bring to bear in the conflict. However, if Russian territorial, personnel, and materiel losses continue to mount without improvements on the battlefield, President Vladimir Putin will face an unpalatable set of choices. In the extreme, the conflict offers plausible scenarios for Russia to become the first state to use nuclear weapons in warfare since 1945. This report evaluates the potential for further escalation in the conflict in Ukraine, including the prospects for escalation to Russian nuclear use. It does so by evaluating Russian and Ukrainian behavior in the conflict to date and identifying and assessing the escalation options still open to both sides. The report is intended to inform U.S. and North Atlantic Treaty Organization (NATO) policymakers as they consider how to avoid further escalation of the conflict while assisting Ukraine in its efforts to defeat the Russian invasion and to better inform the public debate around these issues
Keywords: Prognose; Eskalation; Russisch-Ukrainischer Krieg; Escalation (Military science); Deterrence (Strategy); Geopolitics; Ukraine / History / Russian Invasion, 2022-; Ukraine / Foreign relations / Russia (Federation); Russia (Federation) / Foreign relations / Ukraine; Geopolitical Strategic Competition; North Atlantic Treaty Organization; Russia; Ukraine; United States; Warfare and Military Operations; Escalade (Science militaire); Dissuasion (Stratégie); Géopolitique; Ukraine / Histoire / 2022- (Invasion russe); Ukraine / Relations extérieures / Russie; geopolitics